2017
DOI: 10.1186/s12885-017-3351-0
|View full text |Cite
|
Sign up to set email alerts
|

JS-K, a nitric oxide pro-drug, regulates growth and apoptosis through the ubiquitin-proteasome pathway in prostate cancer cells

Abstract: BackgroundIn view of the fact that JS-K might regulate ubiquitin E3 ligase and that ubiquitin E3 ligase plays an important role in the mechanism of CRPC formation, the goal was to investigate the probable mechanism by which JS-K regulates prostate cancer cells.MethodsProliferation inhibition by JS-K on prostate cancer cells was examined usingCCK-8 assays. Caspase 3/7 activity assays and flow cytometry were performed to examine whether JS-K induced apoptosis in prostate cancer cells. Western blotting and co-imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…NO is often derived from both the endogenous way by stimulating NO syntheses and the exogenous way through NO donor [ 12 ]. O 2 -(2,4-dinitrophenyl) 1-[(4-ethoxycarbonyl)piperazin-1-yl]diazen-1-ium-1,2-diolate (JS-K,C 13 H 16 N 6 O 8 ) is a diazeniumdiolate-based NO donor and is highly cytotoxic to several types of human cancer cells, such as acute lymphoblastic leukemia [ 13 ], hepatocellular carcinoma [ 14 ], prostate cancer cells [ 15 ] or murine erythroleukemia cells [ 16 ]. Moreover, JS-K as a lead NO donor selectively exhibits antitumor effects towards cancer cells while has no significant toxicity toward normal cells [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…NO is often derived from both the endogenous way by stimulating NO syntheses and the exogenous way through NO donor [ 12 ]. O 2 -(2,4-dinitrophenyl) 1-[(4-ethoxycarbonyl)piperazin-1-yl]diazen-1-ium-1,2-diolate (JS-K,C 13 H 16 N 6 O 8 ) is a diazeniumdiolate-based NO donor and is highly cytotoxic to several types of human cancer cells, such as acute lymphoblastic leukemia [ 13 ], hepatocellular carcinoma [ 14 ], prostate cancer cells [ 15 ] or murine erythroleukemia cells [ 16 ]. Moreover, JS-K as a lead NO donor selectively exhibits antitumor effects towards cancer cells while has no significant toxicity toward normal cells [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro experiments indicated that some regulatory mechanisms are involved in various tumors, such as the mitogen-activated protein kinase pathways, which modulate proliferation, motility, and cell death [9]. JS-K promotes apoptosis by inducing ROS production and the ubiquitin-proteasome pathway in human prostate cancer cells [21, 22]. In this study, we showed for the first time that JS-K induced ovarian cancer cells death via an autophagic mechanism in vitro .…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, the occurrence of apoptosis cancer cells is a useful method of treatment. JS‐K as a novel nitric oxide prodrug appears to have cytotoxic effects against various types of human cancers, which is attributed to its capability of releasing high levels of NO . Our previous studies have demonstrated that JS‐K significantly induced apoptosis of HepG2 cells, which were attributed to the high levels of NO production released from JS‐K .…”
Section: Discussionmentioning
confidence: 99%
“…JS-K as a novel nitric oxide prodrug appears to have cytotoxic effects against various types of human cancers, which is attributed to its capability of releasing high levels of NO. [13][14][15] Our previous studies have demonstrated that JS-K significantly induced apoptosis of HepG2 cells, which were attributed to the high levels of NO production released from JS-K. 12 To obtain an insight into the mechanism by which JS-K induces apoptosis we investigated the effect JS-K on the proliferation of HCC cells. In the present study, JS-K exerted more cytotoxic effects in the HepG2 cells than PLC5, Huh-7, Bel-7402, or SMMC-7721 hepatocellular carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%